Business and Technology Incubators and their Role in the Nordic Countries in Comparison to the GCC countries: An Analysis of Current Affairs - Thomas Hedner; Hanadi Almubaraki; Michael Busler; Adli Abouzeedan (European Regional Science Association (ERSA), 2010)
Business and Technology incubators are seen as important actors for the development of dynamic start-up companies in national economies. The way such incubators function and the impact they have on regional development may vary from one region to another. In this paper we survey and discuss the roles played by business and technology incubators in two different regions of the world, namely the Nordic region with countries like Sweden, Norway and Finland and the Gulf Cooperation Council (GCC) countries, such as Kuwait, Bahrain, Qatar, UAE and Saudi Arabia. The business and technology incubators were assessed in terms of perspective (Logics and Function; Strategy and Planning; Policies and Practices; Role and Impact; Output and Outcome) as well as stage of development (Inception, Implementation, Consolidation and Renewal; Etzkowitz and Klofsten 2005). The paper analyzes the role of business incubators from functional and longitudinal perspectives. In the two regions, we have also analyzed the strength and impact of actors and institutions involved in the development of incubator systems, such as academic, business and governmental institutions.
Keywords: 330; Incubators; Business Incubators; venture creation; Nordic countries; GCC countries